Synthesis of pyrrolo[1,2-a]quinolines by formal 1,3-dipolar cycloaddition reactions of quinolinium salts - Choi, Anthony; Morley, Rebecca M.; Coldham, Iain (Beilstein Journal of Organic Chemistry, 2019)
Quinolinium salts, Q+-CH2-CO2Me Br− and Q+-CH2-CONMe2 Br− (where Q = quinoline), were prepared from quinolines. Deprotonation of these salts with triethylamine promoted the reaction of the resulting quinolinium ylides (formally azomethine ylides) with electron-poor alkenes by conjugate addition followed by cyclization or by [3 + 2] dipolar cycloaddition. The pyrroloquinoline products were formed as single regio- and stereoisomers. These could be converted to other derivatives by Suzuki–Miyaura coupling, reduction or oxidation reactions.
Keywords: azomethine ylide; cycloaddition; heterocycle; pyrrolidine; stereoselective

(untitled) - Li, J.; Ye, Y.; Zhang, Y. (Org. Chem. Front., 2018)

(untitled) - Meyer, A. G.; Ryan, J. H. (Molecules, 2016)

(untitled) - Moyano, A.; Rios, R. (Chem. Rev., 2011)

(untitled) - Coldham, I.; Hufton, R. (Chem. Rev., 2005)

(untitled) - Xiong, Y.; Du, Z.; Chen, H.; Yang, Z.; Tan, Q.; Zhang, C.; Zhu, L.; Lan, Y.; Zhang, M. (J. Am. Chem. Soc., 2019)

(untitled) - Filatov, A. S.; Knyazev, N. A.; Shmakov, S. V.; Bogdanov, A. A.; Ryazantsev, M. N.; Shtyrov, A. A.; Starova, G. L.; Molchanov, A. P.; Larina, A. G.; Boitsov, V. M.; Stepakov, A. V. (Synthesis, 2019)

(untitled) - Jia, Z.-J.; Shan, G.; Daniliuc, C. G.; Antonchick, A. P.; Waldmann, H. (Angew. Chem., Int. Ed., 2018)

(untitled) - Feng, B.; Lu, L.-Q.; Chen, J.-R.; Feng, G.; He, B.-Q.; Lu, B.; Xiao, W.-J. (Angew. Chem., Int. Ed., 2018)

(untitled) - Xu, S.; Zhang, Z.-M.; Xu, B.; Liu, B.; Liu, Y.; Zhang, J. (J. Am. Chem. Soc., 2018)

(untitled) - Williams, B. M.; Trauner, D. (J. Org. Chem., 2018)

(untitled) - Zhang, Q.; Zhang, Z.; Huang, Z.; Zhang, C.; Xi, S.; Zhang, M. (Angew. Chem., Int. Ed., 2018)

(untitled) - Otero-Fraga, J.; Suárez-Pantiga, S.; Montesinos-Magraner, M.; Rhein, D.; Mendoza, A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Erguven, H.; Leitch, D. C.; Keyzer, E. N.; Arndtsen, B. A. (Angew. Chem., Int. Ed., 2017)

(untitled) - Hauduc, C.; Bélanger, G. (J. Org. Chem., 2017)

(untitled) - Boissarie, P.; Bélanger, G. (Org. Lett., 2017)

(untitled) - Liu, Y.; Hu, H.; Wang, X.; Zhi, S.; Kan, Y.; Wang, C. (J. Org. Chem., 2017)

(untitled) - Wang, H.; Regan, C. J.; Codelli, J. A.; Romanato, P.; Puchlopek-Dermenci, A. L. A.; Reisman, S. E. (Org. Lett., 2017)

(untitled) - Dong, Z.; Zhu, Y.; Li, B.; Wang, C.; Yan, W.; Wang, K.; Wang, R. (J. Org. Chem., 2017)

(untitled) - Motornov, V. A.; Tabolin, A. A.; Nelyubina, Y. V.; Nenajdenko, V. G.; Ioffe, S. L. (Org. Biomol. Chem., 2019)

(untitled) - Zhang, D.; Lin, L.; Yang, J.; Liu, X.; Feng, X. (Angew. Chem., Int. Ed., 2018)

(untitled) - Day, J.; McKeever-Abbas, B.; Dowden, J. (Angew. Chem., Int. Ed., 2016)

(untitled) - Brioche, J.; Meyer, C.; Cossy, J. (Org. Lett., 2015)

(untitled) - Allgäuer, D. S.; Mayr, H. (Eur. J. Org. Chem., 2013)

(untitled) - Kucukdisli, M.; Opatz, T. (Eur. J. Org. Chem., 2012)

(untitled) - Jacobs, J.; Van Hende, E.; Claessens, S.; De Kimpe, N. (Curr. Org. Chem., 2011)

(untitled) - Tsuge, O.; Kanemasa, S.; Takenaka, S. (Bull. Chem. Soc. Jpn., 1985)

(untitled) - Tsuge, O.; Kanemasa, S.; Takenaka, S. (Bull. Chem. Soc. Jpn., 1985)

(untitled) - An, J.; Yang, Q.-Q.; Wang, Q.; Xiao, W.-J. (Tetrahedron Lett., 2013)

(untitled) - Fernández, N.; Carrillo, L.; Vicario, J. L.; Badía, D.; Reyes, E. (Chem. Commun., 2011)

(untitled) - Han, Y.; Hou, H.; Fu, Q.; Yan, C.-G. (Tetrahedron, 2011)

(untitled) - Dumitrascu, F.; Caira, M. R.; Georgescu, E.; Georgescu, F.; Draghici, C.; Popa, M. M. (Heteroat. Chem., 2011)

(untitled) - Grigg, R.; Heaney, F. (J. Chem. Soc., Perkin Trans. 1, 1989)

(untitled) - Nicolescu, A.; Deleanu, C.; Georgescu, E.; Georgescu, F.; Iurascu, A.-M.; Shova, S.; Filip, P. (Tetrahedron Lett., 2013)

(untitled) - Caira, M. R.; Dumitrascu, F.; Georgescu, E.; Georgescu, F.; Popa, M. M. (Rev. Roum. Chim., 2011)

(untitled) - Jones, R. C. F.; Rafiq, S.; Elsegood, M. R. J.; McKee, V.; Slater, M. J. (Chem. – Asian J., 2010)

(untitled) - Hazra, A.; Mondal, S.; Maity, A.; Naskar, S.; Saha, P.; Paira, R.; Sahu, K. B.; Paira, P.; Ghosh, S.; Sinha, C.; Samanta, A.; Banerjee, S.; et al. (Eur. J. Med. Chem., 2011)

(untitled) - Cappelli, A.; Giuliani, G.; Anzini, M.; Riitano, D.; Giorgi, G.; Vomero, S. (Bioorg. Med. Chem., 2008)

(untitled) - Jones, D. T.; Harris, A. L. (Mol. Cancer Ther., 2006)

(untitled) - Gomha, S. M.; Dawood, K. M. (J. Chem. Res., 2014)

(untitled) - Liu, J.; Yan, P.; Li, Y.; Zhou, Z.; Ye, W.; Yao, J.; Wang, C. (Monatsh. Chem., 2014)

(untitled) - Allgäuer, D. S.; Mayer, P.; Mayr, H. (J. Am. Chem. Soc., 2013)

(untitled) - Wu, L.; Sun, J.; Yan, C.-G. (Org. Biomol. Chem., 2012)

(untitled) - Liu, Y.; Zhang, Y.; Shen, Y.-M.; Hu, H.-W.; Xu, J.-H. (Org. Biomol. Chem., 2010)

(untitled) - Georgescu, E.; Dumitrascu, F.; Georgescu, F.; Draghici, C.; Popa, M. M. (Rev. Roum. Chim., 2010)

(untitled) - Georgescu, E.; Georgescu, F.; Draghici, C.; Caproiu, M. T.; Dumitrascu, F. (Rev. Roum. Chim., 2010)

(untitled) - Dawood, K. M.; Ragab, E. A.; Khedr, N. A. (J. Chin. Chem. Soc., 2009)

(untitled) - Dawood, K. M.; Ragab, E. A.; Mohamed, S. N. (Z. Naturforsch., B: J. Chem. Sci., 2009)

(untitled) - Caira, M. R.; Georgescu, E.; Georgescu, F.; Popa, M. M.; Dumitraşcu, F. (ARKIVOC, 2009)

(untitled) - Shestopalov, A. M.; Chunikhin, K. S.; Rodinovskaya, L. A. (Chem. Heterocycl. Compd., 2002)

(untitled) - Danac, R.; Al Matarneh, C. M.; Shova, S.; Daniloaia, T.; Balan, M.; Mangalagiu, I. I. (Bioorg. Med. Chem., 2015)

(untitled) - Singh, D.; Sinha, P.; Bansal, R. K. (Curr. Green Chem., 2014)

(untitled) - Paira, R.; Mondal, S.; Chowdhury, A.; Banerjee, M.; Maity, A.; Hazra, A.; Mondal, N. B. (Tetrahedron Lett., 2013)

(untitled) - Pospíšil, J.; Trávníček, M.; Potáček, M. (ARKIVOC, 2001)

(untitled) - Matusiak, G.; Śliwa, W. (Monatsh. Chem., 1993)

(untitled) - Sun, J.; Zhang, Y.; Shen, G.-L.; Yan, C.-G. (ChemistrySelect, 2017)

(untitled) - Chen, R.; Zhao, Y.; Sun, H.; Shao, Y.; Xu, Y.; Ma, M.; Ma, L.; Wan, X. (J. Org. Chem., 2017)

(untitled) - Glushchenko, T. P.; Aksenov, A. V.; Goncharov, V. I. (Chem. Heterocycl. Compd., 2009)

(untitled) - Liu, Y.; Hu, H.-Y.; Liu, Q.-J.; Hu, H.-W.; Xu, J.-H. (Tetrahedron, 2007)

(untitled) - Serov, A. B.; Kartsev, V. G.; Aleksandrov, Y. A.; Dolgushin, F. M. (Russ. Chem. Bull., 2005)